Mobilidade no espaço fronteiriço: o caso da fronteira Paraguai-Brasil - Mariana Oeyen (2011)
In the political boundary between Paraguay and Brazil, the residents constantly move across the border from the 1960s and create various forms of movement and flows. This work intends to capture the dynamics of mobility based on reference unit or spatial area: the border. The work seeks to understand the complexity of mobility dynamics in a reference unit in a dynamic area as the border, studying the possible relations between the various types of mobility coexisting (short, medium distance, internal and international, temporal or definitive) in the context of border regions. It identifies and characterizes the historical and current dynamics of mobility (existing types of mobility) on the Paraguay-Brazil border and presents a proposal of typology of motilities as a possible example to verify empirically in the border area between Paraguay and Brazil from the census data and of the qualitative studies developed to date. This angle appears to understand more an intermediate level between micro and macro level, this allows us to identify the variety of shifts (different types of mobility) of people who live and travel in this complex frontier that is the border between Brazil and Paraguay.